Nicotinic Receptor Antagonists as Treatments for Nicotine Abuse - Crooks, Peter A. (2014)
Despite the proven efficacy of current pharmacotherapies for tobacco dependence, relapse rates continue to be high, indicating that novel medications are needed. Currently, several smoking cessation agents are available, including varenicline (Chantix(®)), bupropion (Zyban(®)), and cytisine (Tabex(®)). Varenicline and cytisine are partial agonists at the α4β2* nicotinic acetylcholine receptor (nAChR). Bupropion is an antidepressant but is also an antagonist at α3β2* ganglionic nAChRs. The rewarding effects of nicotine are mediated, in part, by nicotine-evoked dopamine (DA) release leading to sensitization, which is associated with repeated nicotine administration and nicotine addiction. Receptor antagonists that selectivity target central nAChR subtypes mediating nicotine-evoked DA release should have efficacy as tobacco use cessation agents with the therapeutic advantage of a limited side-effect profile. While α-conotoxin MII (α-CtxMII)-insensitive nAChRs (e.g., α4β2*) contribute to nicotine-evoked DA release, these nAChRs are widely distributed in the brain, and inhibition of these receptors may lead to nonselective and untoward effects. In contrast, α-CtxMII-sensitive nAChRs mediating nicotine-evoked DA release offer an advantage as targets for smoking cessation, due to their more restricted localization primarily to dopaminergic neurons. Small drug-like molecules that are selective antagonists at α-CtxMII-sensitive nAChR subtypes that contain α6 and β2 subunits have now been identified. Early research identified a variety of quaternary ammonium analogs that were potent and selective antagonists at nAChRs mediating nicotine-evoked DA release. More recent data have shown that novel, non-quaternary bis-1,2,5,6-tetrahydropyridine analogs potently inhibit (IC(50)<1 nM) nicotine-evoked DA release in vitro by acting as antagonists at α-CtxMII-sensitive nAChR subtypes; these compounds also decrease NIC self-administration in rats.